Understanding Trainers Implementing their Occupational Skill in Delivering Training - Joshi, Pashupati (Journal of Training and Development, 2017)
The objective of this study was to understand the vocational instructional implementation of occupational skill while delivering hardware maintenance training in Kavraplanchok district of Nepal. A case study research design was applied while carrying out this study. All together five participants were purposefully selected for the study. The study reveals that the training was taken for granted by the trainees. Lack of equipment, tools and resources, same teaching learning methodology, focus on tradition lecture methods and limited time frame were the hindering factor during the implementation of occupational skills by the trainers.